Source analysis of quartz from the Upper Ordovician and Lower Silurian black shale and its effects on shale gas reservoir in the southern Sichuan Basin and its periphery, China. (24th March 2018) - Han, Chao; Han, Mei; Jiang, Zaixing; Han, Zuozhen; Li, Hao; Song, Zhigang; Zhong, Wenjian; Liu, Kaixuan; Wang, Chunhao
Abstract : A major breakthrough in shale gas exploration and development has been made concerning the black shale of the Upper Ordovician and Lower Silurian. In recent years, significant progresses have been made regarding the exploration and development of shale gas in the black shale of the Upper Ordovician and Lower Silurian. Accordingly, we investigated the petrological and geochemical characteristics of the black shale from WF2‐LM5 graptolite biozones and performed a source analysis of quartz as well as evaluated its effect on shale gas reservoirs. The black shale mainly contains clay, carbonate, and quartz with the average TOC of 2.21%. Three quartz types, Q1, Q2, and Q3, were identified via petrological and cathodoluminescence (CL) analysis. Q1 of detrital origin as suggested by its typical morphology with monocrystal structure, large grain‐size, subrounded to angular outlines, and clear edges. This is further supported by the occurrence of medium luminescence under cathodoluminescence and medium intensity of P1 and P2 and high intensity P3 according to CL images. Q2 accounts for more than 90% of quartz and exhibits cryptocrystalline texture, an irregular shape, blurring edges, and low luminescence, and its CL images show low intensity P1, low intensity P2, and high intensity P3 . Q3 have the morphologies of siliceous organisms, for example, sponge spicules, radiolaria, and foraminifera. Q2 and Q3 belong to authigenic quartz derived from siliceous organisms. Th/U and V/Cr indicate black shale from LM1–3 mainly deposited in the dysoxic‐anoxic environment while black shale from LM4–5 deposited in the oxic environment. Authigenic quartz‐rich shales from LM1–3 were speculated to be the best shale gas reservoirs characterized by high TOC content, high gas content, and with negligible amount of detrital quartz. Compared with shale from LM1–3, black shale from LM4–5 usually have relatively high detrital quartz content and low TOC content and gas content. Considering the abundant interparticle pore space, the detrital quartz‐rich shale interbedded within the black shale from LM4–5, could also become good shale gas reservoirs if sufficient gas supply is guaranteed.